Peran Brand Image Memoderasi Electronic Word of Mouth (E- Wom) Terhadap Keputusan Pembelian Online di Gorontalo - Rosmina Hiola (Jurnal Indonesia Sosial Sains, 2022)
Advances in information technology and with the advent of online social networking sites, have changed the way consumers get information. This phenomenon has an impact on consumers, because the information is easily accessible and this greatly affects consumer decisions in making purchases. This study aims to examine the role of Brand Image in moderating Electronic Word of Mouth (e-WoM) on purchasing decisions. The research sample is a group of millennials who have Facebook, Shopee and Lazada accounts. The sampling technique used purposive sampling technique with a sample size of 100 respondents. The analysis tool uses regression and moderated regression analysis (MRA). The results showed that Electronic Word of Mouth (e-WoM) had a significant effect on purchasing decisions. Brand Image is able to moderate the influence of Electronic Word of Mouth (e-WoM) on purchasing decisions.